026 Differential Effects on Urethral Function, Epithelial Morphology, and Molecular Profile in Two Different Rat Models of Stress Urinary Incontinence by Simulated Birth Trauma or Estrogen Deficiency. (1st May 2022) - Kurobe, M.; Takaoka, E.; Suzuki, T.; Mizoguchi, S.; Saito, T.; Cao, N.; Alexandre, C.E.; Gotoh, D.; Igarashi, T.; Inamura, S.; Ando, T.; Inai, H.; et al.
ABSTRACT: Introduction: Stress urinary incontinence (SUI) is the common type of urinary incontinence with a significantly negative impact on quality of life, including sexual dysfunction, in women. Although the etiology of SUI in women seems to be multifactorial, multiple vaginal parities and estrogen deficiency (ED) are considered to be major risk factors of SUI in elderly women. Thus, animal models of simulated birth trauma induced by multiple vaginal distention (VD) and ED induced by bilateral ovariectomy (OVX) have been used to study the SUI pathophysiology in rats. In previous studies, bilateral ovariectomy (OVX) reportedly induces the morphological changes in the rat urethral epithelium. It has also been reported that serotonergic (5HT + ) paraneurons uniquely located in the urethra modulate urethral sensory function and that their numbers decrease in aged or diabetes rats. However, the difference of changes in the urethra such as those in epithelial morphology and expression of 5HT + paraneurons in the urethra, in these two models has not been well characterized. Objective: We therefore evaluated the histological changes of the urethral epithelium and 5HT + cell expression, and urethral continence function in rats with OVX-induced ED or VD-induced simulated birth trauma. Methods: Nulliparous SD rats were divided into: (1) sham group; (2) OVX 3-weeks group; (3) OVX 6-weeks group; (4) VD-1 group (1 time VD 2 weeks before assays); (5) VD-3 group (3 times VDs every 2 weeks). VD was induced by balloon catheter inflation for 4 hours in the vagina under isoflurane anesthesia. Urethral function was evaluated by the amplitude of urethral pressure responses during sneezing (A-URS) and urethral baseline pressure (UBP), which was measured by a microtransducer-tipped catheter inserted into the mid-urethra (n=6, each group). Following the urethral function analysis, the mid urethra was harvested, and the tissue sections (10 μm) were stained with Hematoxylin-eosin (H&E) and anti-5HT antibodies for immunofluorescent detection of 5HT + paraneurons. In addition, in separate groups of rats, changes in urethral mRNA levels of tryptophan hydroxylase-1 (TPH1), a key enzyme of 5HT synthesis, were quantified by RT-PCR (n=6, each group). All data are represented as means ± SE. P < 0.05 was considered significant. Results: OVX 6-weeks and VD-3 rats exhibited significant decreases in UBP and A-URS vs. sham (Fig. 1A). The mean epithelial thickness was significantly decreased in OVX 3, 6-weeks, VD-1 and 3 rats (Fig 1B, C) vs. sham. The number of urethral 5HT + paraneurons was significantly decreased in OVX 3, 6 weeks, VD-1 and 3 rats (Fig. 2A, B) vs. sham. TPH-1 mRNA levels were significantly decreased in OVX 3, 6-weeks and VD-3 rats (Fig. 2C) vs. sham. Conclusions: These results indicate that urethral epithelial atrophy and loss of 5HT + paraneurons occur prior to SUI- inducing urethral dysfunction in both models, with the changes being rapid and greater in OVX compared to VD. These histological changes in the urethra may contribute to the establishment of SUI in ED and multiple birth trauma. Disclosure: Work supported by industry: no.